2007
DOI: 10.1562/0031-8655(2001)0730024mwsiot2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Multi-waveband Solar Irradiance on Tree-shaded Vertical and Horizontal Surfaces: Cloud-free and Partly Cloudy Skies¶

Abstract: Irradiance measurements of short wave (SW), photosynthetically active (PAR), ultraviolet‐A (UVA) and ultraviolet‐B (UVB) solar radiations were made on horizontal and vertical surfaces in the shade of trees under cloud‐free and partly cloudy skies. All measurements were referenced to the irradiance of a horizontal surface above the canopy. For horizontal shaded surfaces under cloud‐free skies, the values of the ratio (Rh) of below‐ to above‐canopy horizontal irradiance were similar for the UVA and UVB wavebands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…This is also reported by others who recommend reducing and protecting open sides . The amount of sky obscuration provided by the different environments can be determined with the use of upward‐facing hemispherical photographs with appropriate image analysis . In addition, for the larger SZA, the shade cast by the small structure moved away from underneath the shade where generally seating may be provided.…”
Section: Factors Influencing Shade Uv Protectionmentioning
confidence: 59%
See 1 more Smart Citation
“…This is also reported by others who recommend reducing and protecting open sides . The amount of sky obscuration provided by the different environments can be determined with the use of upward‐facing hemispherical photographs with appropriate image analysis . In addition, for the larger SZA, the shade cast by the small structure moved away from underneath the shade where generally seating may be provided.…”
Section: Factors Influencing Shade Uv Protectionmentioning
confidence: 59%
“…An extensive amount of research has been conducted quantifying UV levels beneath different shade environments ( e.g . ). The fact that shade is an essential component of UV minimization means that these environments must be better designed and constructed based on research that shows how UV radiation interacts with these environments.…”
Section: Introductionmentioning
confidence: 97%
“…Shade is considered as one of the main protection strategies against the sun radiation. But it has been appreciated that people under tree, 28–31 hair, 32 cloud, 28,31 shade structure, 33,34 or beach umbrella 33,35,36 shade are exposed to considerable amount of scattered UV radiation 33 . Herein, evaluation of SED reduction by ‘town’ shade, buildings or trees, varied from 51% to 97%.…”
Section: Discussionmentioning
confidence: 99%
“…It could also be attributed to the fact that most of the measurement days had little in the way of cloud cover. Previous studies showed measured PFs for a large tree decreased from 32 to 10 depending upon the amount of cloud and therefore scattered UVB present (18) and that cloudy conditions tended to increase the UVB in the shade compared with under cloud‐free conditions (5), thus reducing protection. Table 2 shows the measurements of ambient solar UVR in SEDs made locally on the open lawn of the arboretum for the 2 h period near solar noon.…”
Section: Resultsmentioning
confidence: 99%